An Experimental Approach to the Measurement of Wall Pressure Generated by an Underwater Spark-Generated Bubble by a Hopkinson Bar - Xiongliang Yao; Xiongwei Cui; Kai Guo; Yingyu Chen (Shock and Vibration)
The wall pressure loading due to the underwater spark-generated bubble, having served as an efficient technique to study the underwater explosion, has drawn much attention. Compared with the numerical study of the pressure characteristics, the direct experimental investigation is much rarer. Recently, an improved pressure-measuring system by using a Hopkinson pressure bar as the sensing element is proposed, set up, and validated by the current authors. In this article, the improved methodology and experimental system is used to detect and analyze the pressure loading on the target plate surface due to the underwater spark-generated bubble beneath the plate. A series of experiments with 3 mm, 5 mm, 10 mm, 15 mm, …, 60 mm standoffs are carried out. The experimental results and the related analysis and discussions are presented. Based on the results, the improved methodology can be used to detect the pressure loading due to the spark-generated bubble. There is multipeak oscillation near the peak of the shock pressure loading profile. The peak pressure versus the standoff is also summarized. According to the characteristics of the induced water jet pressure and the bubble-collapse pressure loading given in this article, enough attention should be paid to not only the jet and the first bubble-collapse pressure loadings but also the secondary bubble-collapse pressure loadings especially when the dimensionless distance γ>1.